Hidden features: CD36/SR-B2, a master regulator of macrophage phenotype/function through metabolism - Chen, Yuge; Zhang, Xuejia; Huang, Shengbin; Febbraio, Maria (Frontiers in Immunology, 2024)
Once thought to be in a terminally differentiated state, macrophages are now understood to be highly pliable, attuned and receptive to environmental cues that control and align responses. In development of purpose, the centrality of metabolic pathways has emerged. Thus, macrophage inflammatory or reparative phenotypes are tightly linked to catabolic and anabolic metabolism, with further fine tuning of specific gene expression patterns in specific settings. Single-cell transcriptome analyses have revealed a breadth of macrophage signatures, with some new influencers driving phenotype. CD36/Scavenger Receptor B2 has established roles in immunity and lipid metabolism. Macrophage CD36 is a key functional player in metabolic expression profiles that determine phenotype. Emerging data show that alterations in the microenvironment can recast metabolic pathways and modulate macrophage function, with the potential to be leveraged for therapeutic means. This review covers recent data on phenotypic characterization of homeostatic, atherosclerotic, lipid-, tumor- and metastatic-associated macrophages, with the integral role of CD36 highlighted.